2014
DOI: 10.1371/journal.pone.0099719
|View full text |Cite|
|
Sign up to set email alerts
|

Rapamycin Is Neuroprotective in a Rat Chronic Hypertensive Glaucoma Model

Abstract: Glaucoma is a leading cause of irreversible blindness. Injury of retinal ganglion cells (RGCs) accounts for visual impairment of glaucoma. Here, we report rapamycin protects RGCs from death in experimental glaucoma model and the underlying mechanisms. Our results showed that treatment with rapamycin dramatically promote RGCs survival in a rat chronic ocular hypertension model. This protective action appears to be attributable to inhibition of neurotoxic mediators release and/or direct suppression of RGC apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 52 publications
1
63
1
1
Order By: Relevance
“…Under this experimental condition treatment with the autophagy inducer rapamycin exerted protective effects, while autophagy inhibition exacerbated axonal damage (Kitaoka et al, 2013). Vice versa, in the same glaucoma model induced by laser photocoagulation, Su et al (2014) reported a significant reduction of RGC loss following treatment with rapamycin.…”
Section: Endogenous Pro-survival Pathways and Neuroprotectionmentioning
confidence: 75%
“…Under this experimental condition treatment with the autophagy inducer rapamycin exerted protective effects, while autophagy inhibition exacerbated axonal damage (Kitaoka et al, 2013). Vice versa, in the same glaucoma model induced by laser photocoagulation, Su et al (2014) reported a significant reduction of RGC loss following treatment with rapamycin.…”
Section: Endogenous Pro-survival Pathways and Neuroprotectionmentioning
confidence: 75%
“…Although autophagy and apoptosis can coexist in the same damaged RGC, they do not necessarily overlap and can occur independently [58,92]. Autophagy can occur before neuronal apoptosis in aluminum-insulted astrocytes, a chronic hypertensive glaucoma model, and an optic nerve axotomy mouse model [46,93,94]. Similarly, in a chronic glaucoma model, autophagy activation occurs earlier than RGC loss [58].…”
Section: Cross-talk Between Autophagy and Apoptosismentioning
confidence: 99%
“…This interaction may be due to a relief of negative feedback loop from the mTOR signaling pathway. 26 Akt is closely associated with cellular survival, 42 and the levels of phosphorylated Akt are decreased in the eyes with experimental glaucoma 43 and after excitotoxicity in RGCs. 44 Thus, enhanced phosphorylation of Akt in the retina may have beneficial effects on the RGCs.…”
Section: Discussionmentioning
confidence: 99%